A missense mutation in CLIC2 associated with intellectual disability is predicted by in silico modeling to affect protein stability and dynamics - Shawn Witham; Kyoko Takano; Charles E. Schwartz; Emil Alexov (2011)
Large-scale next generation resequencing of X chromosome genes identified a missense mutation in the CLIC2 gene on Xq28 in a male with X-linked intellectual disability (XLID) and not found in healthy individuals. At the same time, numerous nsSNPs (nonsynonomous SNP) have been reported in the CLIC2 gene in healthy individuals indicating that the CLIC2 protein can tolerate amino acid substitutions and be fully functional. To test the possibility that p.H101Q is a disease-causing mutation, we performed in silico simulations to calculate the effects of the p.H101Q mutation on CLIC2 stability, dynamics, and ionization states while comparing the effects obtained for presumably harmless nsSNPs. It was found that p.H101Q, in contrast with other nsSNPs, (a) lessens the flexibility of the joint loop which is important for the normal function of CLIC2, (b) makes the overall 3D structure of CLIC2 more stable and thus reduces the possibility of the large conformational change expected to occur when CLIC2 moves from a soluble to membrane form, and (c) removes the positively charged residue, H101, which may be important for the membrane association of CLIC2. The results of in silico modeling, in conjunction with the polymorphism analysis, suggest that p.H101Q may be a disease-causing mutation, the first one suggested in the CLIC family.